Role of Cultural Heritage in Luxury Fashion Branding in South Africa - Mpilo, Desmond (International Journal of Fashion and Design, 2024)
Purpose: The aim of the study was to analyze the role of cultural heritage in luxury fashion branding in South Africa. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The role of cultural heritage in luxury fashion branding in South Africa has become increasingly significant as brands seek to integrate local identity with global luxury standards. Cultural elements, such as traditional patterns, textiles, and craftsmanship, are being incorporated into luxury fashion, reflecting South Africa’s rich heritage and fostering a sense of authenticity and exclusivity. This approach not only strengthens brand identity but also appeals to both local and international consumers who value unique, culturally embedded products. However, challenges include ensuring respectful representation and avoiding cultural appropriation. Unique Contribution to Theory, Practice and Policy: Cultural capital theory, brand heritage theory, symbolic consumption theory may be used to anchor future studies on the role of cultural heritage in luxury fashion branding in South Africa. Fashion brands in South Africa can enhance their market positioning by leveraging unique cultural elements that resonate both locally and globally. Policymakers should create frameworks that ensure cultural elements are not exploited by global fashion brands without proper attribution and compensation to local communities.